2021
DOI: 10.1007/s00414-021-02674-0
|View full text |Cite
|
Sign up to set email alerts
|

How safe is BDSM? A literature review on fatal outcome in BDSM play

Abstract: A noteworthy number of people are interested in BDSM (bondage and discipline, dominance and submission, sadism, and masochism). Fatal outcomes while participating in BDSM activities occur. The aim of this literature review is to give a better insight into potential dangerous BDSM play by summarizing published data on BDSM fatalities. A literature search was conducted. It was searched for non-natural death related to BDSM activity. Seventeen cases were found. The age of the deceased ranged between 23 and 49 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…Given its prevalence and frequency, sexual choking may be the most common form of choking/strangulation in the U.S., and it disproportionately impacts women. Yet, aside from case reports and media articles describing unintentional death from consensual sexual choking (e.g., Roma et al, 2013;Schori et al, 2022;Zemek, 2021), and one study demonstrating a cross-sectional relationship between a history of having been choked and poorer mental health (Herbenick et al, 2022a), little is known about potential health sequelae from being choked during sex. Building on prior research related to strangulation in other contexts, a goal of the present study was to characterize sexual choking, how it is enacted, and the physical responses people notice from having been choked.…”
Section: Physical Responses Of Choking/strangulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its prevalence and frequency, sexual choking may be the most common form of choking/strangulation in the U.S., and it disproportionately impacts women. Yet, aside from case reports and media articles describing unintentional death from consensual sexual choking (e.g., Roma et al, 2013;Schori et al, 2022;Zemek, 2021), and one study demonstrating a cross-sectional relationship between a history of having been choked and poorer mental health (Herbenick et al, 2022a), little is known about potential health sequelae from being choked during sex. Building on prior research related to strangulation in other contexts, a goal of the present study was to characterize sexual choking, how it is enacted, and the physical responses people notice from having been choked.…”
Section: Physical Responses Of Choking/strangulationmentioning
confidence: 99%
“…A recent review of fatal outcomes in BDSM found that strangulation accounted for most of the reported fatalities (Schori et al, 2022). Most people will have insufficient training to attend to someone should they lose consciousness, experience a seizure or cardiac arrest, or become unresponsive while being choked.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Consequently, what people tend to refer to as sexual choking may share at least some health risks as those arising from strangulation occurring in other contexts, such as the so-called “choking game,” sexual assault, or intimate partner violence (IPV) (Bichard et al, 2022 ; Busse et al, 2015 ). These risks may include neck bruising, neck edema, recurrent headaches, tinnitus, alterations in consciousness, and—in rare cases—death (Herbenick et al, 2022a ; Schori et al, 2022 ). In this paper, we use the term sexual choking to refer to strangulation that occurs during sex.…”
Section: Introductionmentioning
confidence: 99%
“…While fatalities from consensual sexual choking/strangulation are rare, they do occur (Schori et al, 2022 ) and have been documented since at least the 1700s (Tarr, 2016 ). A recent review of deaths from partnered bondage and discipline/dominance and submission/sadism and masochism (BDSM) practices found that most case reports (88%) resulted from manual or ligature strangulation (Schori et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Strangulation, even with non-fatal intentions, carries inherent health risks. For example, strangulation was identified as the most common cause of death in Bondage, Discipline, Dominance, Submission, Sadism, and Masochism (BDSM)-related fatalities in a literature review of case reports from 1986 to 2020 (Schori et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%